2021
DOI: 10.21873/anticanres.15442
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitor as a Therapeutic Choice for Double Cancer: A Case Series

Abstract: Background: Hepatocellular carcinoma (HCC) occasionally presents with simultaneous or metachronous primary malignancies of other organs. Despite the limited scope of cytocidal anticancer drugs or molecular targeted agents, immune checkpoint inhibitors (ICIs) can still be used for various malignancies. Here, we present cases of double cancers including HCC treated with ICIs. Case Report: Case 1: A 70-year-old man with lung cancer and 80-mm HCC underwent nivolumab therapy. The sizes of both cancers remained cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Only one report has shown the efficacy of atezolizumab in HCC and esophageal cancer. 13 In that report, HCC treatment demonstrated a partial response and the esophageal cancer stabilized, and the patient remained healthy for 9 months with treatment.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Only one report has shown the efficacy of atezolizumab in HCC and esophageal cancer. 13 In that report, HCC treatment demonstrated a partial response and the esophageal cancer stabilized, and the patient remained healthy for 9 months with treatment.…”
Section: Discussionmentioning
confidence: 88%
“… 14 Recently, the efficacy of nivolumab was reported in a patient with HCC and lung cancer. 13 Persistent partial response of HCC and lung cancer was sustained for 9 months.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, regarding ICI treatment for MPMs, there have been only a few case reports available and evidence-based studies are lacking. There are several immune checkpoint inhibitors, such as nivolumab, pembrolizumab, and atezolizumab, which have demonstrated encouraging efficacy in the treatment of multiple primary tumors (26)(27)(28)(29)(30). A bulk of studies have shown the favorable efficacy of ICIs on PSC (31)(32)(33) and HCC (34)(35)(36), respectively.…”
Section: Discussionmentioning
confidence: 99%